Optic neuropathy in craniosynostosis - Estrela, Tais; Dagi, Linda R. (Frontiers in Ophthalmology, 2024)
Craniosynostosis (CS) or the premature fusion of one or more cranial sutures in utero, or during the first years of life, can present in isolation or as a multisystem clinical disorder with a particular impact on visual function. Among ophthalmic complications, optic neuropathy is a significant cause of irreversible vision loss in these patients.Children with CS are at higher risk of developing elevated intracranial pressure which can lead to papilledema and, ultimately, optic atrophy. In addition, sometimes associated obstructive sleep apnea, abnormalities in central nervous system venous development, and Chiari malformation may contribute to optic neuropathy. Ophthalmologists have an important role in managing a number of coexistent ophthalmologic complications such as strabismus, anisometropia, amblyopia, ptosis, and exposure keratopathy in addition to maintaining surveillance for early signs of optic neuropathy; they play a critical consultative role contributing to the decision for primary or repeat decompressive surgery.In this article, we aim to review the etiology, diagnostic approach, and management of optic neuropathies in patients with craniosynostosis.